(untitled) (Journal of Basic and Applied Research in Biomedicine, 2024)
Hormonal contraceptives are commonly used by women of reproductive age and may be associated with an increased risk of thromboembolism. Any rise in the relative risk of venous thromboembolism related to specific contraceptive formulations could lead to a notably elevated absolute risk. This study seeks to evaluate the potential role of Factor V Leiden (FVL) and Prothrombin G20210A mutations as risk factors for thromboembolism in users of hormonal contraceptives in Benin City. The study population consisted of 50 non-contraceptive users, 50 non-hormonal contraceptive users, 50 progestin-only contraceptive users, and 50 combined oral contraceptive users recruited from Family Planning Clinics in Benin City. Each participant provided aseptically collected venous blood, with 5.0 mL collected in total. 0.5 mL was placed in a container containing 3.1% tri-sodium citrate anticoagulant for the manual determination of Prothrombin time (PT) and activated partial thromboplastin time (APTT). Additionally, 0.5 mL of venous blood was dispensed into a plain container with 0.25 mL DNA-RNA shield solution for the detection of Factor V Leiden and Prothrombin 20210A gene mutations using PCR Duplex Prothrombin 20210 and Factor V. Data analysis was conducted using the statistical package for social sciences (SPSS) version 17.0 software. The findings revealed that the overall mutation carriage rate (AA and AG) for the Prothrombin 20210A gene (5%) was more prevalent than FVL (3%) among the subjects. Furthermore, the mean PT and APTT (in seconds) were significantly lower (p<0.001) among women using combined hormonal contraceptives. These findings suggest a potential association between the presence of FVL and FII genes mutations and thromboembolism among Nigerian women using hormonal contraceptives.